Pengaruh Campuran Fly ash dan Variasi Kapur terhadap Daya Dukung Tanah Bekas Tambang di Gunung Sarik - Ereza Apriyani; Syahril Rahmat (JOURNAL SAINS STUDENT RESEARCH, 2026)
The limited availability of land suitable for development has encouraged the utilization of alternative land, one of which is ex-mining land. Soil in ex-mining areas generally has low bearing capacity and therefore does not meet the technical requirements for construction subgrade. This study aimed to analyze the effect of adding fly ash and lime on increasing the bearing capacity of ex-mining soil in Gunung Sarik Village, Kuranji District, Padang City. The soil damples used were disturbed soils collected from the ex-mining area. Fly ash was obtained from the Teluk Sirih Steam Power Plant, West Sumatra, while quicklime was sourced from the Bukit Tui Factory, Pdang Panjang City. The research was conducted through laboratory testing including physical properties analysis, Proctor compaction test, and California Bearing Ratio (CBR) laboratory testing based on ASTM D 1883-67 standards. The mixture variations consistes of 5% fly ash combined with 0%, 4%, 8%, and 12% lime. The addition of fly ash and lime positively influenced the increase in soil bearing capacity. The CBR value of native soil, Which was 10,37%, increased across all mixture variations. The highest increase was achieved with the combination of 5% fly ash and 12% lime, reaching a CBR value of 19,16%, followed by the mixture of 5% fly ash and 8% lime at 14,43%, and 5% fly ash with 4% lime at 14,21%. These results indicate thet the addition of fly ash and lime is effective in increasing the bearing capacity of ex-mining soil through the stabilization process, making the soil feasible for consideration as construction subgrade.